Homogeneous Components of a CDH Fuzzy Space - Samer Al Ghour (International Journal of Electrical and Computer Engineering (IJECE), 2019)
We prove that fuzzy homogeneous components of a CDH fuzzy topological space  (X,T) are clopen and also they are CDH topological subspaces of its 0-cut topological space (X,T0).